2014
DOI: 10.1016/j.bpj.2013.11.960
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contributions of Nonmuscle Myosin II Isoforms and Functional Domains to Stress Fiber Mechanics

Abstract: Synaptic stimulation leads to expansion of the dendritic spine caused by rearrangement of the actin cytoskeleton triggered by phosphorylation of the calcium calmodulin dependent kinase (CaMKII) and by myosin II activity. To study CaMKII-actomyosin interactions we have visualized single GFP-tagged CaM-KII holoenzymes bound to tagRFP-tagged cortical actin in human endothelial cells by total internal reflection fluorescence microscopy. CaMKII phosphorylation mutants were used to examine whether release of CaMKII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…By contrast, peripherally located SFs such as the ones severed in our experiments are primarily regulated by myosin light chain kinase and are thus expected to be minimally perturbed by ROCK manipulation (17,18). To suppress ROCK activity and dissipate central connections, we treated cells with 5 μM Y-27632.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…By contrast, peripherally located SFs such as the ones severed in our experiments are primarily regulated by myosin light chain kinase and are thus expected to be minimally perturbed by ROCK manipulation (17,18). To suppress ROCK activity and dissipate central connections, we treated cells with 5 μM Y-27632.…”
Section: Resultsmentioning
confidence: 96%
“…We then applied SLA on SFs along the FN-free edge and observed their retraction kinetics. As in our previous studies, we fit each retraction curve to a Kelvin-Voigt viscoelastic cable model described by a time constant (τ), which reflects the SF's effective viscosity/ elasticity ratio, and a plateau retraction distance (L o ), which correlates to the elastic energy dissipated by half of the severed SF (3,17,18) (Fig. 1D) (see SI Text and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3 regimes allow independent regulations and force transmission pathways that are structurally and functionally segregated. Previous studies had shown that myosin IIA structures are primarily controlled by Rho/Rock/MLC whereas myosin IIB structures are mainly regulated by Ca ++ /calmodulin/MLCK (Chang and Kumar, 2015;Kassianidou et al, 2017;Kuragano et al, 2018;Morin et al, 2014;Totsukawa et al, 2004). Phosphorylation studies using purified myosin II indicate that MLCK phosphorylates myosin IIB more efficiently than ROCK, whereas the reverse is true for myosin IIA (Amano et al, 1996;Sandquist et al, 2006).…”
Section: Discussionmentioning
confidence: 99%